Forming Methods of Ornithonyms in Uzbek and English Languages - Maxmudova, Nargiza (Miasto Przyszłości, 2023)
In this article, ornithonyms in Uzbek and English languages are etymologically and semantically analyzed, and compared in the method of comparison. Phraseological and paremiological units, which are specific units of the language, contain cultural information about the history, traditions and daily life of the people who speak this language.